Pengaruh Faktor Keuangan dan Non Keuangan terhadap Financial Sustainability Ratio Perbankan - Nurhikmah, Suci; Rahim, Rida (Journal of Management and Business Review, 2021)
The design of this study is the design of hypothesis testing. The population of this study includes all private non-foreign exchange national commercial banks for the period 2013-2019. The sample selection technique uses purposive sampling method and research data obtained by 18 banks. The data analysis method used is regression analysis with panel data. The results of this study indicate: Capital Adequacy Ratio (CAR) has negative and insignificant effect, then Non Performing Loans (NPL), Operating Costs to Operating Income (BOPO), Loan to Deposit Ratio (LDR), Inflation, and Company Size (Size) insignificant positive effect. While Return on Assets (ROA) is the only variable that has a positive and significant influence on the financial sustainability ratio (FSR). The adjusted R square value of 0.236, shows that the Financial Sustainability Ratio (FSR) is influenced by Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Return On Assets (ROA), Operating Costs to Operating Income (BOPO), Capital Adequacy Ratio (CAR), Inflation, and Company Size (Size) of 23.6%, while the remaining 76.3% is influenced by other factors not examined in this study. The results of this study can be used to carry out further research, and add insight into banking knowledge, particularly in banking financial performance. So that investors/customers can more easily make decisions with the information on theÂ  financial performance of the company concered.